The impact of photodynamic therapy on immune system in cancer – an update - Dudzik, Tomasz; Domański, Igor; Makuch, Sebastian (Frontiers in Immunology, 2024)
Photodynamic therapy (PDT) is a therapeutic approach that has gained significant attention in recent years with its promising impact on the immune system. Recent studies have shown that PDT can modulate both the innate and adaptive arms of the immune system. Currently, numerous clinical trials are underway to investigate the effectiveness of this method in treating various types of cancer, as well as to evaluate the impact of PDT on immune system in cancer treatment. Notably, clinical studies have demonstrated the recruitment and activation of immune cells, including neutrophils, macrophages, and dendritic cells, at the treatment site following PDT. Moreover, combination approaches involving PDT and immunotherapy have also been explored in clinical trials. Despite significant advancements in its technological and clinical development, further studies are needed to fully uncover the mechanisms underlying immune activation by PDT. The main objective of this review is to comprehensively summarize and discuss both ongoing and completed studies that evaluate the impact of PDT of cancer on immune response.